STUDY OF THE GROWTH Al© DISSOLUTION OF COPER WHISKERS - Hayes, Eric (My University, 1965)
Copper whiskers were grown by the chemical reduction of cuprous iodide by hydrogen using Brenner’s technique.^43 The whiskers were dissolved electrolytically in acidified copper sulphate at a current density of 1.5 micro-amps per square cm. The etched cross-sectional profiles were used to determine the dissolution rate of major orientations.